Amory Austin collection relating to heraldry - Austin, Amory
Correspondence, notes, notebooks, and other papers relating to heraldry. Also includes a letter to Ivers James Austin, a Massachusetts politician, and his obituary.
Collection material in English.
Collector.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Austin, Ivers James, -- 1808-1889.; Heraldry; Collectors